Water supply in the remote area of Tumbuk Darat, Malaysia - Megat Mohd Noor, Megat Johari; Jusoh, Ahmad; Zakaria, Mohamad Pauzi; Ghazali, Abdul Halim (1987)
Provision of safe water supply for the rural areas in Malaysia is still inadequate. The rural populaion constitutes 65% of the total of which 50% has yet to be provided with safe water. This paper intends to present the findings of a study help at Tumbuk Darat, a typical village experiencing an acute water supply problem. Background survey was done prior to obtaining the baseline data of the water quality of the available source. The factors contributing to the problem and identification of possible water sources were the major areas of the study. Recommendation of appropriate technology for the village was made after taken into consideration both the technical and human factors. Two sources namely rainwater and groundwater were identified as suitable for the village community. The present rainwater harnessing however requires the installation of a simple foul flush diversion device to improve its quality. As for the groudwater is concerned, deep well extraction yields better quality. Minimal treatment consisting of aeration and direct filteration is recommended to render it fit for consumption.